Tools for critical thinking in biology - Jenkins, Stephen H. (Oxford University Press, 2015)
The American Association for the Advancement of Science's report on Vision and Change in Undergraduate Biology Education suggests that instructors ""can no longer rely solely on trying to cover a syllabus packed with topics"" but rather should ""introduce fewer concepts but present them in greater depth."" They further suggest that the principles embodied in a set of core concepts and competencies should be the basis for all undergraduate biology courses, including those designed for nonmajors. The theme of Tools for Critical Thinking in Biology will be the first and most fundamental of these.